Perceptions of automated data collection technology use in the construction industry - Majrouhi Sardroud, Javad (Journal of Civil Engineering and Management, 2014)
Research projects have indicated development of several technical solutions for the management of construction activities. However, little attention has been paid to the issues regarding the adoption and implementation of these techniques. This study investigates the perception of Automated Data Collection (ADC) technology usage in construction, and identifies reasons why available ADC technology has not been fully introduced in construction. A comprehensive literature review carried out in this research identifies barriers to the adoption of ADC technology. In total, 19 key factors are identified as barriers for adoption of ADC technology in construction, and validated through an international questionnaire survey. According to the results, process related factors play an essential role in adopting automated data acquisition technologies in the construction industry. In order to form the backbone of technology adoption in real scenarios, and to identify driving factors in this field, this paper also introduces an implementation framework for ADC technology in the construction industry.